A ressignificação da atividade de leitura em Língua Inglesa: experiência em uma escola pública - Cunha, Mara Cristina Ferreira (2013)
This work aims to describe and interpret the phenomenon ressignification of the English reading activity of a high school students group in a public school in the city of São Paulo in classes planned with the contribution from these students. The theoretical basis of this research relied on texts about the reading activity (Grellet, 1981/1985; Nuttall, 1982/1985; P. Freire, 1993/2007, Kleiman, 2011, 2012) and collaborative learning (P. Freire, 1970/2010; Magalhães, 2011). This research was conducted in the light of Hermeneutic-Phenomenological Approach (van Manen, 1990; Freire, 1998, 2009, 2010, 2012). Questionnaires, a reflexive reports, reflexive questions, reflexive diaries and field notes are the instruments for text collection. The interpretation of the texts points to three main themes which appear as central in this lived experience: disinterest, interest and challenges, and these themes present subthemes which express the desire to study the English language, resistance to classes based on tasks which are common in public schools, such as translation and grammar, and invest their focus in activities meaningful to their lives, and see the teacher as a partner when she/he gives them voice. Thus, this research aims to contribute to the area of teaching-learning, providing information about this English reading activity as a lived experience held in and through collaboration of the students